A Holistic Approach to Developing Spiritual Life through Islamic Religious Organizations at Madrasah Aliyah under the Joint Decree of Three Ministers in Bingkat - Putri, Tasya Billah; Hasan, Ibrahim (Aksara Shofa, 2025)
The importance of spiritual education in shaping student character in Islamic-based schools, such as Madrasah Aliyah SKB 3 Menteri Bingkat, as well as the challenges faced in integrating Islamic values into students' daily lives. This study used a qualitative method with a phenomenological approach to explore students' experiences in developing spiritual life through Islamic spiritual organizations. The purpose of this study was to understand the impact of the holistic approach in spiritual education and assess the effectiveness of using various technology-based learning media, including mobile applications, e-learning platforms, learning videos, audio podcasts, web-based interactive resources, ebooks, and education-specific social media. The results showed that this holistic approach significantly improved students' understanding and practice of Islamic teachings. Technology-based learning media proved effective in making religious learning more engaging, accessible and interactive, thereby increasing student motivation and understanding. Support from family and community also plays an important role in strengthening students' spiritual experiences. The conclusion of this study is that a holistic approach that incorporates various learning media and environmental support is an effective strategy to develop students' spiritual lives in Islamic-based schools.